Monoclonal Antibodies in Light of Mpox Outbreak: Current Research, Therapeutic Targets, and Animal Models - Vladimir N. Nikitin; Iuliia A. Merkuleva; Dmitriy N. Shcherbakov (Antibodies)
The rapid rise in monkeypox virus infections among humans from 2022 to 2024 has captured the attention of the global healthcare community. In light of the lack of mandatory vaccination and limited data on next-generation vaccines for monkeypox prevention, the urgent development of therapeutic agents has become a priority. One promising approach involves the use of neutralizing monoclonal antibodies. This review highlights significant advancements in the search for antibodies against human pathogenic orthopoxviruses, particularly focusing on their potential application against the monkeypox virus. We also analyze viral proteins that serve as targets for identifying therapeutic antibodies capable of neutralizing a wide range of viruses. Finally, we deemed it essential to address the challenges associated with selecting an animal model that can adequately reflect the infectious process of each orthopoxvirus species in humans.